Synergy Between Value Methodology and Continuous Improvement - Ekechi Sixtus Nshirim (CV. Multi Kreasi Media, 2022)
Every company strives to maximize return on investment by combining distinct industrial engineering techniques, such as value engineering, continuous improvement methodologies, six sigma, theory of constraints, 5s and other industrial engineering techniques. This article emphasizes a comprehensive approach to improve a process by looking at how value engineering and lean six sigma overlap. Despite the limits of value engineering and lean concepts, the integrated approach looks for places where both techniques could be used together to increase the advantages that go beyond what is attainable with a single strategy. Value engineering and lean six sigma research looks at the advantages and disadvantages of both methodologies and identifies places where they might complement one another. The study of these methods pinpoints areas in which value engineering and lean concepts complement each other. Continuous improvement strategies have advanced as evidenced by the formalization of activities, their distribution across disciplines, and the introduction of hybrid approaches. The development of hybrid techniques, in particular lean and value engineering, is the main topic of this study. It is recommended that hybrid techniques be implemented using interchangeable use, concurrent use, and integrated use models; however, the literature neither provides distinct model definitions nor a formal framework to guide model selection. This framework's goal is to make implementation easier and lay a consistent foundation for future growth, which will ultimately lead to better and more successful long-term implementation.